Computed tomography and magnetic resonance tomography in cases of coronary heart disease - Lackner, K; Krahe, T; Neubauer, S; Ertl, G (1990)
MR has replaced CT in cardiology as a tomographic examination method with the exception of the identification and differentiation of cardiac calcifications. MR combines good morphological visualization with function diagnostics and biochemical informations. Both methods are inappropriate for diagnosing diseases of the coronary vessels.